Article 24 of the African Charter on Human and Peoples' Rights: an individual or peoples' right to a satisfactory environment? - Longo, Evan (AUC Knowledge Fountain, 2011)
Article 24 of the African Charter on Human and Peoples' Right has been viewed similarly to the individual right to a satisfactory environment within international law. The African Charter however differs from the broader conception of the right to a satisfactory environment by expressing the right as a peoples' and not an individual right. Unlike previous authors, I argue that the fact that article 24 of the charter characterizes the right, as a peoples' right is significant and cannot be ignored. The SERAC v. Nigeria communication in the African commission is the only time in which the right to a satisfactory environment has been significantly dealt with in the African Commission. The case articulated the substantive aspects of article 24 but was also important for its understanding of the concept of peoples'. This paper seeks to clarify the similarities and differences in the conception of a right to a satisfactory environment in the universal and African systems of human rights. It will explore the question of why article 24 is structured as a peoples' right and not an individual right, and how this articulation of the right may be useful or problematic in the African context. I argue that because of the collective nature of article 24, the peoples' right to a satisfactory environment in the African Charter has deep connections with modern forms of foreign oppression, and other collective rights, particularly the right to self-determination. In order to demonstrate this I will describe the right to a satisfactory environment as it is conceived generally in international law and more specifically within Africa. Next, I will examine the concept of peoples' and its connection with the right to self-determination, as it is understood generally in international law and particularly in Africa. I will then explain the functions of article 24 and its place in the African Charter as a peoples' right. Finally, I will examine the strengths and weaknesses of conceiving the right to a satisfactory environment as a collective right and what conclusions may be drawn for current and future articulations of the right.